Environmental drivers and plant species diversity in the Catalan and Andorran Pyrenees - Ninot, Josep M.; Ferré, Albert; Grau, Oriol; Font, Xavier; Pérez-Haase, Aaron; Carrillo, Empar (Lazaroa, 2013)
In this paper, we analyse the spatial distribution of plant diversity in the Pyrenean area of Catalonia and Andorra, in parallel to the distribution of landscape descriptors that have been proven to be related to species distribution. We used a wide range of synthetic parameters that refer to physiography (area, main outcrops), bioclimate (length of the growing season, rainfall, potential evapotranspiration), and landscape structure (habitats richness and diversity). Plant diversity was mainly assessed through the data gathered in the Biodiversity Data Bank of Catalonia, which consists of over 300,000 records of 2,335 species of vascular plants. Spatial variation in all the aspects covered here was analysed separately for eight sectors in the study area, and along the altitudinal gradient. Among the abiotic factors, bioclimatic parameters stood out for their regular variation –increasing or decreasing– along the altitudinal gradient. Noticeable differences were found between sectors, and were related to their physiographic particularities or location within the Pyrenees. Along the altitudinal gradient we found consistent shifts in the distribution of functional, ecological and phytogeographic plant groups. As for species richness, all the Pyrenean sectors gave a roughly similar pattern in the altitudinal gradient, with the maximum values found at low-medium altitudes and a regular decreasing trend towards the summits, coinciding with a steep decrease in habitats richness. Differences between sectors in plant diversity mostly depended on the altitude span of each and of other mid-scale landscape singularities, and were more evident between axial Pyrenean and pre-Pyrenean sectors. However, these regional differences also respond to historical biogeography, which is the foundation for understanding the altitudinal distribution of plants through species migration, extinction, and diversification over major Quaternary climatic variation.